Characterization Of Stroke Using MRI Diffusion Technique - A. Ibrahim; C. Edward; H. Osman; A. ELzaki (Asian Journal of Medical Radiological Research, 2013)
Diffusion weighted imaging DWI is an Magnetic Resonance imaging (MRI) technique in which microscopic water motion is responsible for thecontrast within the image. The aim of the current study was to assess the accuracy and sensitivity of spin lattice relaxation time (T1), spin- spinrelaxation time (T2), Flair and Diffusion MR techniques in the diagnosing of the stroke, carried at AlZaytona specialist hospital in Khartoum, 25MRI brain images were selected (13 male and 12 female) with the age range 40-89 who were diagnosed clinically as stroke. MRI was performedwith the T1, T2, Flair and were additionally evaluated with diffusion-weighted techniques. one Radiologist was chosen to avoid intra-experiencevariation. The main results of this study were found that, (DWI) and T2 weighted images techniques had similar accuracy of 100%and sensitivityof 71.4% in diagnosing the stroke. MRI FLAIR technique had sensitivity of 68.75% and accuracy of 88% where T1 weighted images has the leastaccuracy and sensitivity as 32%and 44.4 % respectively , also study showed that the most affected age range 50-59 years. The study concludedthat the diffusion and T2 weighted images are highly accurate for diagnosing stroke